Database Management Systems and Use of Digital Resources in Some Selected Public University Libraries of Bangladesh: An Overview (Bangladesh Journal of Library and Information Science, 2012)
This paper Discuses present status of database management practices and use of digital resources of five selected Public University Libraries of Bangladesh. Survey has been carried out on the names of used software, number of databases for the dissemination of library resources with total number of records, subscription of online journals with other digital and electronic resources, number of current/bound journals, computers, CDs and audiovisual materials etc. The objectives, methodology for collection, presentation and analysis of collected data for this study and highlights the meaning, need, main considerations, components and domain of library automation in the context of surveyed libraries also have been described. The development of digital technology combined with the evolution of Internet has prompted significant changes in library services and operations within the last few years. The study tries to focus on the availability of hardware and software in the respective library, examine types and forms of library collections, various house keeping operations, management, services, and library administration etc. It has also put forward some suggestions for the future development of the surveyed libraries. Bangladesh Journal of Library and Information Science Vol.2(1) July 2012 pp.67-78DOI: http://dx.doi.org/10.3329/bjlis.v2i1.12923